FEMALE STUDENTS’ VOCABULARY KNOWLEDGE LEVEL ON ENGLISH LOANWORDS IN BAHASA INDONESIA - Febriza, Tesa (ELP (Journal of English Language Pedagogy), 2024)
This research aims to assess and analyze the vocabulary knowledge level of female students on English loanwords in Bahasa Indonesia, specifically in the domains of fashion and cosmetics. The focus is on female students at the fifth semester of the English Department at UIN Sjech M. Djamil Djambek Bukittinggi, as they are thought to use more loanwords and have an affinity for modern trends. The research population consisted of 81 students from the English education department, and a purposive sampling technique was used to select a sample of 59 female students. The research data were obtained from the Vocabulary Knowledge Scale (VKS) test, adapted from Paribakht and Wesche, which combines self-reports with performance-based evidence. The instrument was analyzed statistically using the formula f=p/n×100. Data were collected using the Vocabulary Knowledge Scale (VKS) test and analyzed statistically. The findings revealed that generally, the students' vocabulary knowledge level on English loanwords was at level four, indicating they could recognize the loanwords, knew their meanings and synonyms in Bahasa Indonesia, and could translate them back into English. However, they struggled to produce grammatically and contextually correct sentences using the loanwords. This suggests that while students demonstrated a good understanding of English loanwords, they are not yet fully able to use them effectively as a vocabulary learning strategy, highlighting the need for further emphasis on active usage in appropriate contexts.